Aging in the sebaceous gland - Hou, Xiaoxiao; Wei, Ziyu; Zouboulis, Christos C; Ju, Qiang (Frontiers in Cell and Developmental Biology, 2022)
Sebaceous glands (SGs) originate from hair follicular stem cells and secrete lipids to lubricate the skin. The coordinated effects of intrinsic and extrinsic ageing factors generate degradation of SGs at late age. Senescence of SGs could be a mirror of late ageing of both human body and skin. The procedure of SGs ageing goes over an initial SGs hyperplasia at light exposed skin areas to end with SGs atrophy, decreased sebum secretion and altered sebum composition, which is related to skin dryness, lack of brightness, xerosis, roughness, desquamation and pruritus. During differentiation and ageing of SGs many signaling pathways, such as Wnt/β-catenin, c-Myc, AhR, p53, are involved. Random processes lead to random cell and DNA damage due to the production of free radicals during lifespan, neuroendocrine system alterations. Extrinsic factors include sunlight exposure (photoaging), environmental pollution and cigarette smoking, which can directly activate signal pathways such as Wnt/β-catenin, Notch, AhR and p53, and are probably associated with the de-differentiation and hyperplasia of SGs, or indirectly activate the above-mentioned signal pathways by elevating the inflammation level. The production of ROS during intrinsic SGs aging is less, the signal pathways are activated slowly and mildly, sebocytes are still differentiated, yet terminal differentiation is not completed, with extrinsic factors, relevant signal pathways are activated rapidly and fiercely, thus inhibiting the differentiation of progenitor sebocytes and even induce the differentiation of progenitor sebocytes into keratinocyte. Methods in The managements of SGs ageing are also mentioned.